2003
DOI: 10.1016/s0002-9440(10)63908-9
|View full text |Cite
|
Sign up to set email alerts
|

API2-MALT1 Fusion Defines a Distinctive Clinicopathologic Subtype in Pulmonary Extranodal Marginal Zone B-Cell Lymphoma of Mucosa-Associated Lymphoid Tissue

Abstract: t(11;18)(q21;q21) is associated with mucosa-associated lymphoid tissue (MALT)-type lymphoma and results in API2-MALT1 fusion. However, its clinicopathologic significance remains unclarified. API2-MALT1 fusion is detected most frequently in MALT lymphomas primarily involving the lung. We therefore screened 51 cases of pulmonary MALT lymphoma for API2-MALT1 fusion, and studied its relationship with clinicopathologic factors including the immunohistochemical expression of BCL10, another MALT lymphoma-associated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
70
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 42 publications
6
70
0
1
Order By: Relevance
“…A precise microscopic observation revealed that 46 of 60 cases were 'typical' in histology. 1,25 However, seven cases showed an increased number of large cells (5%olarge cells o10%, without solid or sheet-like proliferations), and seven cases exhibited marked plasmacytoid differentiation (plasmacytoid tumor cells 490%). The mean age of MALT lymphoma patients was 62.1 years with a range of 31-94 years.…”
Section: Case Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…A precise microscopic observation revealed that 46 of 60 cases were 'typical' in histology. 1,25 However, seven cases showed an increased number of large cells (5%olarge cells o10%, without solid or sheet-like proliferations), and seven cases exhibited marked plasmacytoid differentiation (plasmacytoid tumor cells 490%). The mean age of MALT lymphoma patients was 62.1 years with a range of 31-94 years.…”
Section: Case Selectionmentioning
confidence: 99%
“…Some of the tumors in this series were included in our previous study. 25 Extraction of Genomic DNA and Total RNA On examination of tissue sections under a dissecting microscope, selected areas were retrieved using a serial H&E section as a guide. Genomic DNA and total RNA were extracted in digestion buffer containing proteinase K as previously described.…”
Section: Case Selectionmentioning
confidence: 99%
See 3 more Smart Citations